Unit Shift Dalam Novel The Sea Of Monsters - Lia Nurmalia; Danang Dwi Harmoko; Prapti Wigati Purwaningrum (Wanastra: Jurnal Bahasa dan Sastra, 2021)
The objectives of the research are to know the translation shift and the translation equivalence in The Sea of Monsters novel which is translated into “Laut Para Monster”. This research uses qualitative method through content analysis approach. The writers compared the source text (ST) and the target text (TT) then, did the analysis by using theories proposed by (Catford,1965) and  (Nida,1982). The results show that the most shifting is unit shift, 65% and it reaches 77% formal equivalence. Those results show that TSu is well transferred into TSa in term of form and content. It can be seen from the translation shift which only happen at the word level, it seems that the translator is faithful to source text, while seen by the translation equivalence, seems that the writer is also faithful to target text.